Dietary flavonoids form supramolecular assemblies, alter biochemistry, and enhance cell resilience - Reilly, Charles B.; Bernier, Sylvie G.; Shahriar, Sanjid; Horvath, Viktor; Lewandowski, Michael; Javorsky, Emilia; Budnik, Bogdan; Ingber, Donald E. (Frontiers in Nutrition, 2025)
Flavonoids, a diverse class of polyphenols found in many plant-based foods, are increasingly recognized for their health benefits, including antioxidant and anti-inflammatory activities. Recent evidence links higher dietary flavonoid diversity with reduced all-cause mortality and improved outcomes in chronic diseases. Yet, due to concerns about non-specific binding, their exclusion from drug development pipelines has limited deeper mechanistic understanding. Here, we show how flavonoids may promote cellular resilience by forming supramolecular assemblies that interact with proteins. Using molecular dynamics simulations (MDS) and in vitro assays, we found that different flavonoids self-assemble into ordered structures that influence protein structural dynamics and fiber formation. These structures have differential effects on enzyme activity and cell viability under stress. The ability to undergo supramolecular assembly may be important as flavonoids protect human cells against ultraviolet radiation-induced damage through a non-antioxidant mechanism. These findings suggest that supramolecular assembly and structural heterogeneity of flavonoids may underlie their diverse bioactivities and help to explain how the diversity of dietary flavonoids can support adaptive changes in cellular biochemistry, enhance resilience to environmental stressors, and improve human health.